(untitled) (Symposium on Natural and Applied Sciences, 2026)
The modern higher education landscape is undergoing rapid transformation due to globalization, technological innovation, and increasing demand for quality education. Universities are facing growing challenges in managing financial resources effectively, ensuring transparency, and maintaining accountability. In this context, improving financial management based on digital technologies has emerged as a critical strategy for enhancing efficiency, reducing operational costs, and supporting sustainable institutional development.